Offshore wind project-level monitoring in the Northeast U.S. continental shelf ecosystem: evaluating the potential to mitigate impacts to long-term scientific surveys - Methratta, Elizabeth T.; Lipsky, Andrew; Boucher, Jason M. (Frontiers in Marine Science, 2023)
Offshore wind will generate much needed renewable energy in the U.S. and worldwide, but this industry will also affect other ocean uses. In the Northeast U.S. continental shelf (NES) ecosystem, these effects include the impact that wind development will have on the design and execution of long running scientific surveys conducted by National Marine Fisheries Service of the National Oceanic and Atmospheric Administration (NOAA Fisheries) which play a critical role in the provision of scientific information for stock assessment and advice for fisheries management. Recognizing these impacts, the federal government has established a Survey Mitigation Strategy that identifies a need to evaluate whether the information yielded from project-level monitoring studies conducted by wind developers might be suitable for integration with data from NOAA Fisheries surveys, thereby ameliorating the impacts to the surveys. To address this need, we compiled and tabulated information from all currently available project-level monitoring studies and compared elements of the design and methodology of each study with that of the comparable NOAA Fisheries survey. Based on this information, we evaluated their suitability for filling expected gaps in long term surveys, for addressing impacts at the population level, and for understanding interactions between fish stocks and habitat alterations. We found that project-level monitoring studies as currently designed for the NES ecosystem will not yield information that can mitigate impacts to NOAA Fisheries scientific survey time series from offshore wind development. We provide recommendations on how to enhance the ability of project-level monitoring studies to mitigate impacts to long term scientific surveys.